2005
DOI: 10.1007/s10040-004-0395-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropic effects on hydrochemical characteristics of the Valle de Toluca aquifer (central Mexico)

Abstract: The Valle de Toluca aquifer, located in the Highlands of Mexico, is subject to intensive exploitation to meet the water demand in the valley, as well as for part of Mexico City. This intensive exploitation has produced a decline in groundwater level, land subsidence problems and a decrease in river and spring flows. This study is aimed at determining the extent to which the intensive groundwater abstraction is able to affect and modify the chemical characteristics of the water, using statistical techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…Spatially analyzing the data, it was observed that Ca From the values obtained in this study, it could be concluded that the hydrogeochemical feature of the water in the area of study is the predominance of bicarbonate and sodium ions, which is consistent with other studies in the Toluca Valley [3,6,10,11]. The relative abundances of the major ions in water were found in the following order: Na + >Mg 2+ >Ca 2+ >K + =HCO 3 ->>Cl ->SO 4 2-.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Spatially analyzing the data, it was observed that Ca From the values obtained in this study, it could be concluded that the hydrogeochemical feature of the water in the area of study is the predominance of bicarbonate and sodium ions, which is consistent with other studies in the Toluca Valley [3,6,10,11]. The relative abundances of the major ions in water were found in the following order: Na + >Mg 2+ >Ca 2+ >K + =HCO 3 ->>Cl ->SO 4 2-.…”
Section: Resultssupporting
confidence: 89%
“…The presence of sulfates and chlorides was low, although on average this was higher, indicating a recharge of surface water caused by rainwater infiltration. The water according to the Piper diagram was similar to that obtained in the campaigns conducted in previous decades regarding NaHCO 3 and/or Mg(HCO 3 ) 2 , indicating that the groundwater hydrochemistry in this area had not undergone major changes until then. However, Esteller and Andreu [3] analyzed historical anthropogenic impacts and hydrogeochemical characteristics of the Valley of Toluca aquifer, and concluded that the intense exploitation of this aquifer had caused a change in the groundwater hydrochemistry.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations